La ceramica a pareti sottili dalla necropoli di Gazzo Veronese (Verona). Note preliminari dalle indagini 2014/2015 - Scalzeri, Marina; Zentilini, Elisa (Rei Cretariae Romanae Fautorum Acta, 2022)
The University of Verona started the archaeological investigation in Gazzo Veronese in 2014 with the study of the Via Claudia Augusta in the area of Verona. Right from the beginning of the excavation several graves were discovered thus implying the presence of a cemetery. During the following years further burials were in fact brought to light dating back to the 1st century AD. The tombs, mostly cremations, contain typical grave goods: pottery for eating and drinking (olpai, cups, dishes, glass), lamps, coins, glass balsamaria and some personal objects. This contribution focuses on thin walled pottery, which is extremely common in Northern Italy and also in Gazzo Veronese. Their decoration and surface treatment are characteristic of the products of the kiln of Via Platina in Cremona where we think the above mentioned items were produced.